Factors associated with severity and outcomes of diabetic foot ulcers: A single center hospital-based cross-sectional observational study in Eastern India - Anjani Kumar; Bijay Nanda Naik; Vishnu Shankar Ojha; Ratnadeep Biswas; Manoj Kumar; Prathyusha Kokkayil; Kiran Jyoth; Rajdeep Porel (Journal of Family Medicine and Primary Care)
Background: Diabetes mellitus (DM) affects millions globally and is associated with high morbidity, risk of infection, and potential for severe outcomes. In India, where the prevalence of diabetic foot complications is notably high, data on factors influencing the severity and outcomes of diabetic foot ulcers (DFUs) in specific regions, particularly Eastern India, remain sparse. Methods: This hospital-based cross-sectional study included Type 2 DM patients aged over 18 years, excluding those unwilling to participate and those with ulcers classified as Wagner grade less than 2. The study involved the complete enumeration of eligible patients presenting with DFUs. Clinical and demographic data were collected, including glycemic control, physical activity levels, and microbial cultures from ulcer specimens. Results: The study included 90 patients with a mean age of 56.1 years. Most participants were male (76.7%), with 47.8% receiving regular diabetes treatment and only 10% achieving good glycemic control. Positive swab cultures were found in 68.9% of patients, predominantly mono-microbial. Higher grade ulcers were associated with male gender (AOR 5.715), and positive swab cultures (AOR 17.470). Moderate-to-severe physical activity (AOR 9.683) and paresthesia (AOR 0.101) were significant predictors of gangrene, with absent distal pulses (COR 13.818) also indicating a higher risk for gangrene. Good glycemic control was associated with a reduced risk of gangrene (COR 0.125). Conclusions: Maintaining good glycemic control is crucial in preventing complications such as gangrene. Physical activity is generally beneficial in DM; however, excessive or high-impact activities may exacerbate existing foot ulcers and increase the risk of gangrene.